(3GdEOGQI GdeGdjI GdeJbOeIs - (3YOfGf GdJGjg(B, (3GdfYjejs; (3GQTO aDGO GdJejej(B, s ((3YeGf(B:s (3OGQ GdjGRhQj GdYdejI(B,s, 2009)
(3ebOeI aj GdacQ GdeGdj GdeYGUQ, eaGgje aj GdGOGQI GdeGdjI GdeJbOeI, Jbjje GdCOhGJ GdeGdjI WhjdI GdCLdI, bQGQGJ GdGSJKeGQ GdQCSeGdj, bQGQGJ GdJehjd, bQGQGJ ebShe GdCQHGMs
(3HHdjhZQGajG(B: (3U(B.510s
Keywords: (3GdEOGQI GdeGdjI, GdGSJKeGQ, GdJehjds